The effect of COVID-19 on absolute neutrophil counts in patients taking clozapine - Siobhan Gee; David Taylor (SAGE Publishing, 2020)
Clozapine is associated with haematological side effects, including neutropaenia, which can signal impending life-threatening agranulocytosis. Patients with COVID-19 infection frequently experience lymphopaenia, but not neutropaenia. We present 13 patients established on clozapine who developed COVID-19 infection. There were no significant differences in total white cell or neutrophil counts between pre-COVID-19, intra-COVID-19 or post-COVID-19 periods. We therefore suggest that patients who develop COVID-19 should generally have their clozapine treatment continued. Patients taking clozapine who develop neutroapaenia during COVID-19 infection should be investigated and monitored as in normal practice, because changes in neutrophil counts cannot be assumed to be due to the viral infection.